A PEFKS- and CP-ABE-Based Distributed Security Scheme in Interest-Centric Opportunistic Networks - Fei Wang; YongJun Xu; Lin Wu; Longyijia Li; Dan Liu; Liehuang Zhu (International Journal of Distributed Sensor Networks)
Security is a crucial issue in distributed applications of multihop wireless opportunistic network due to the features of exposed on the fly communication, relaxed end-to-end connectivity, and vague destinations literately. In this paper, we focus on problems of user privacy leakage and end-to-end confidentiality invasion in content-based or interest-centric wireless opportunistic network. And we propose a public-encryption-with-fuzzy-keyword-search- (PEFKS-) and ciphertext-policy-attribute-based-encryption- (CP-ABE-) based distributed security scheme by refining and compromising two-pairing-based encryption, searchable encryption, and attribute-based encryption. Our scheme enables opportunistic forwarding according to fuzzy interests preserving full privacy of users and ensures end-to-end confidentiality with a fine-grained access control strategy in an interest-centric scenario of large-scale wireless opportunistic networks. Finally, we analyze and evaluate the scheme in terms of security and performance.